Transformation of Islamic Communication: Optimizing Blockchain Technology for Digital Da'wah Content - Desiana, Desiana (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This research aims to understand the potential and implementation of blockchain technology in the transformation of Islamic communication, particularly in the dissemination of digital da'wah content. This research uses a qualitative method with a descriptive approach. The data collection process was carried out using documentation study tools, observation, and interviews to delve into in-depth information related to the dissemination of digital da'wah content. The research results show that the application of blockchain provides significant benefits for preachers and content creators, such as copyright protection through smart contracts, enhancing the credibility of da'wah content, and expanding audience reach. Blockchain technology, which supports encryption and decentralization systems, secures data from unauthorized access, thereby increasing user trust. This study contributes to the optimization of technology use, specifically blockchain technology, in digital da’wah content. The implications of this research highlight the importance of using technology to support and facilitate the dissemination of da’wah in the digital era. Penelitian ini bertujuan untuk memahami potensi dan implementasi teknologi blockchain dalam transformasi komunikasi Islam, terutama dalam penyebaran konten da'wah digital. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Proses pengumpulan data dilakukan menggunakan alat studi dokumentasi, observasi, dan wawancara untuk menggali informasi mendalam terkait penyebaran konten dakwah secara digital. Hasil penelitian menunjukkan bahwa bahwa penerapan blockchain memberikan manfaat signifikan bagi pendakwah dan pembuat konten, seperti perlindungan hak cipta melalui kontrak pintar, meningkatkan kredibilitas konten dakwah, dan memperluas jangkauan audiens. Teknologi blockchain yang mendukung sistem enkripsi dan desentralisasi membuat data aman dari akses tidak sah, sehingga meningkatkan kepercayaan pengguna. Studi ini berkontribusi pada optimalisasi penggunaan teknologi terkhusus teknologi blockchain pada konten dakwah digital. Implikasi dari penelitian ini menyoroti pentingnya penggunaan teknologi untuk mendukung dan mudahnya diseminasi dalam dakwah di era digital.